2009
DOI: 10.1002/ajpa.21070
|View full text |Cite
|
Sign up to set email alerts
|

mtDNA variability in two Bantu‐speaking populations (Shona and Hutu) from Eastern Africa: Implications for peopling and migration patterns in sub‐Saharan Africa

Abstract: In this study, we report novel data on mitochondrial DNA in two of the largest eastern Bantu-speaking populations, the Shona from Zimbabwe and the Hutu from Rwanda. The goal is to evaluate the genetic relationships of these two ethnic groups with other Bantu-speaking populations. Moreover, by comparing our data with those from other Niger-Congo speaking populations, we aim to clarify some aspects of evolutionary and demographic processes accompanying the spread of Bantu languages in sub-Saharan Africa and to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…The human leukocyte antigens (HLA) has been used for several decades as genetic markers to analyze populations coming from different geographic regions, to investigate the relationships among them and to study human migration that occurred in the past [1,3,4], in addition to their essential roles in histocompatibility and disease susceptibility [5,6]. HLA genes are located on the short arm of human chromosome 6 (6p21.3), its protein products localize at the cell surface where they play key role in immune function [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…The human leukocyte antigens (HLA) has been used for several decades as genetic markers to analyze populations coming from different geographic regions, to investigate the relationships among them and to study human migration that occurred in the past [1,3,4], in addition to their essential roles in histocompatibility and disease susceptibility [5,6]. HLA genes are located on the short arm of human chromosome 6 (6p21.3), its protein products localize at the cell surface where they play key role in immune function [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this level of diversity, however, there is a high level of similarity between groups. 20 The increase in the rate of identification of slowly mutating NRY binary markers (ie, unique event polymorphisms (UEPs)) [21][22][23] has resulted in many studies designed to investigate the paternally mediated genetic relationships of sub-Saharan African populations. Scozzari et al 24 and Underhill et al 25 found UEP (M2 and its analogues such as DYS271G) present at high frequencies specifically in sub-Saharan Africa and suggested this marker as a signature of EBSP.…”
Section: Introductionmentioning
confidence: 99%
“…There is also a unique distribution pattern of mtDNA haplotypes across Africa with some lineages restricted to specific geographical regions and/or language families (Fig. 3) (Newman 1980;Vigilant 1990Vigilant , 1991Chen et al 1995Chen et al , 2000Ehret 1995Ehret , 2006Watson et al 1996Watson et al , 1997Rando et al 1998;Krings et al 1999;Richards et al 2000;Pereira et al 2001;Salas et al 2002;Thomas et al 2002;Destro-Bisol et al 2004;Kivisild et al 2004;Beleza et al 2005;Coia et al 2005;Jackson et al 2005;Cerny et al 2006Cerny et al , 2008Cerny et al , 2009Gonzalez et al 2006;Batini et al 2007;Gonder et al 2007;Behar et al 2008;Coudray et al 2008;Quintana-Murci et al 2008Castri et al 2009;Coelho et al 2009;Poloni et al 2009;Saunier et al 2009;Stefflova et al 2009;Veeramah et al 2010). Additionally, there is also a predominance of some Y chromosome and mtDNA lineages in specific regions of Africa.…”
Section: Mtdna and Y Chromosome Variationmentioning
confidence: 99%